Employee Readiness for Change and Organizational Support as Keys to Successful Banking Transformation - Malinda Sari Sembiring (TALENTA Publisher, Universitas Sumatera Utara, 2024)
The digital era brings a wave of change that requires banks to be able to quickly adapt and transform. New technologies, new business models and evolving customer expectations provide the foundation for banking to remain competitive and relevant now and in the future. Human resource factors are one of the keys to success in facing change, organizational effectiveness and optimization are needed to maintain and increase work engagement and employee readiness in facing change. This research aims to test and analyze the influence of employee readiness to change on organizational transformation through organizational support as a moderating variable. The population in the study were permanent employees in the Sharia Business Unit of PT. North Sumatra Bank. The research method used is quantitative descriptive. Primary data was collected through a survey of 131 permanent employees in the Sharia Business Unit of PT. Bank Sumut, uses proportional random sampling technique. The collected data was analyzed using descriptive statistical analysis and Moderated Regression Analysis (MRA). The research results show that employee readiness to change has a positive and significant influence on organizational transformation. This indicates that increasing employee readiness in making changes will have a positive impact on the effectiveness and success of the transformation process in the Sharia Business Unit. However, this research also proves that organizational support is unable to moderate the relationship between employee readiness and organizational transformation. These findings indicate that organizational support felt by employees is not strong enough to strengthen the influence of employee readiness on organizational transformation.